Nine treatments of Metaldehyde in water / Azlina Mat Saad..[et al.] - Mat Saad, Azlina; Dahalan, Farrah Aini; Abu Hassan Asari, Fadli Fizari (2018)
Metaldehyde is widely applied in the agricultural sector, largely in the removal of snails and slugs. Its water-soluble characteristic causes the compound to end up in our watery system. This is very dangerous as it is able to pollute drinking water and food source; thus adversely affect our health. Hence, removing metaldehyde is an important task for those involved with the treatment of water. For this reason, this paper gathers nine various methods which are proposed and used in treating water contaminated with metaldehyde. The simple but significant explanation will be able to assist those who are new in the fields of pesticide removal and water treatment. In parallel, it will be the basis for more advanced researches in the future.